BIDANGKUASA DAN KEDUDUKAN MAHKAMAH SYARIAH DI MALAYSIA PASCA ALAF 20: KE ARAH MANA? - Mohamed Adil, Mohamed Azam (Jurnal Syariah, 2019)
Much have been discussed about the jurisdiction of Shari’ah Courts in Malaysia. There have been cases in the past, whereby Civil Courts interfered with the jurisdiction of Shari’ah Courts eventhough after the amendment of Article 121 (JA) of the Federal Constitution took place. As the main objective of the amendment was to take away the Civil Courts’ jurisdiction over matters within the Shari’ah Court’s jurisdiction, recent development whereby Civil Courts claiming its’ jurisdiction over the Shari’ah Courts is probably against the abovesaid amendment. This article highlights the issues surrounding the cases decided recently.